2020
DOI: 10.1093/cid/ciaa225
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Neonatal 2019 Coronavirus Disease in China

Abstract: In December 2019, the coronavirus disease (COVID-19) caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) emerged in China and now has spread in many countries. Pregnant women are a population susceptible to COVID-19 and are more likely to have complications and even progress to severe illness. We report a case of neonatal COVID-19 in China with pharyngeal swabs testing positive by real-time reverse-transcription polymerase chain reaction assay 36 hours after birth. However, whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
549
2
57

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 469 publications
(623 citation statements)
references
References 13 publications
15
549
2
57
Order By: Relevance
“…Only three newborns with the Novel coronavirus were reported, by 1 March 2020 [6]. Case one was 17-day-old with fever, cough and vomiting [8], the second case was 5-day-old with fever [6], and the third case was 36-h asymptomatic [5]. These neonates had a positive history of COVID-19 in their mothers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only three newborns with the Novel coronavirus were reported, by 1 March 2020 [6]. Case one was 17-day-old with fever, cough and vomiting [8], the second case was 5-day-old with fever [6], and the third case was 36-h asymptomatic [5]. These neonates had a positive history of COVID-19 in their mothers.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past two decades, SARS-CoV and MERS-CoV have resulted in more than 10,000 deaths [3,4]. Some articles have considered pregnant women as a high-risk group of COVID-19 [5]. But the latest data in UptoDate suggest that pregnancy is not an additional risk factor for the infection, and the risk of disease, treatment and prognosis is similar to that of nonpregnants [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…48,49 Multiple individual case reports as well as descriptions of cohorts of pregnant women with COVID-19 have been published describing their clinical course, laboratory and radiological findings, and details of their birthing by cesarean section or, in fewer cases, vaginal delivery. [20][21][22][23][24][25][26][27][28][29][30][31][50][51][52][53] There have now been at least 108 pregnant women with COVID-19 reported which also describe the clinical and laboratory features of the majority of their newborn infants including virologic status for SARS-CoV-2. 54 Thus far, there have been no laboratory confirmed cases of intrauterine transmission of SARS-CoV-2 from an infected mother to her fetus.…”
Section: Sars-cov-2 and Covid 19mentioning
confidence: 99%
“…54 There have been a few cases in which early neonatal infection with SARS-CoV-2 has occurred, but because testing of neonates was delayed from between 30 hours until 2 days following delivery it cannot be definitively established that they developed COVID-19 prior to delivery and their infection may have occurred in the interval between delivery and testing. 29,53 In a single case laboratory testing of a newborn performed at 2 hours following delivery from a mother with COVID-19 revealed that the infant had developed IgM and IgG specific antibodies to SARS-CoV-2 together with elevated cytokines, but multiple nasopharyngeal swabs from the infant were negative for the virus. 31 A variety of specimens have also been tested using rtPCR for the presence of SARS-CoV-2 following delivery of women with COVID-19 -these include placenta, umbilical cord blood, amniotic fluid, maternal blood, vaginal secretions and breastmilk -and all have been negative for the virus.…”
Section: Sars-cov-2 and Covid 19mentioning
confidence: 99%